2022
DOI: 10.1007/s13304-022-01381-8
|View full text |Cite
|
Sign up to set email alerts
|

Robotic vs laparoscopic approach for single anastomosis duodenal-ileal bypass with sleeve gastrectomy: a propensity score matching analysis

Abstract: Biliopancreatic diversion with duodenal switch and single anastomosis duodenal-ileal bypass with sleeve gastrectomy (SADI-S) are technically demanding hypo-absorptive bariatric procedures. They are often indicated in superobese patients (BMI ≥ 50 kg/m2), as robotic platform could improve ergonomics against a thick abdominal wall, preventing bending of instruments and simplifying hand-sewn anastomoses. We aimed to report our experience with robotic SADI-S (R-group) and to compare outcomes with the laparoscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…As a matter of fact, some studies speci cally underlined that the docking step is responsible for a signi cant increase of OT [32,33]. In our previously experience we underlined that despite robotic technology-associated longer OT, surgical complications are comparable to laparoscopy [14].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…As a matter of fact, some studies speci cally underlined that the docking step is responsible for a signi cant increase of OT [32,33]. In our previously experience we underlined that despite robotic technology-associated longer OT, surgical complications are comparable to laparoscopy [14].…”
Section: Discussionmentioning
confidence: 84%
“…We also showed that, when cases series on a long-time period are considered, differences among laparoscopic and robot-assisted procedures in terms of hospital stay may be explained by variation of clinical protocol (e.g. ERAS fast track protocol), distance between hospital and patients' home and cultural behaviour [14].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Patients were discharged 24 h after the surgical procedure if the following conditions were met: no clinical complications or postoperative biochemical and imaging alterations occurred; oral alimentation was tolerated; autonomous in life activities; the discharge was accepted by the patient. The complete post-operative and follow-up protocol has been previously described in detail and is beyond the scope of this study ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…A standardized postoperative protocol tailored to bariatric patients was used [ 10 , 12 ]. The severity of postoperative complications was graded according to the Clavien-Dindo classification [ 13 ].…”
Section: Methodsmentioning
confidence: 99%